MANAJEMEN PESERTA DIDIK DI LEMBAGA PENDIDIKAN ISLAM - luthfi, muhammad luthfi sya'bana; Muhammad Dhiyaurrahman Hanafi; Zamzami Dhiyaul Ulum; Moh.Ibnu Sholeh (AL-MAFAZI: JURNAL MANAJEMEN PENDIDIKAN ISLAM, 2024)
Judging from its effectiveness as an educational institution, educational problems often arise as a result of improper management. The purpose of this research is to explain the management of students in schools and universities in general. The method used in this study used the library research method or approach. Data analysis was carried out by researchers using data analysis proposed by Miles and Huberman quoted from data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that (1) Student management includes; analysis of student needs, recruitment of new students, selection of new students, orientation of new students, placement of new students, grouping of students, student discipline, and student guidance and counseling services. (2) The management of students is carried out directly by the leadership of the pesantren, the principal and deputy principal who are responsible for the program. Steps in implementing student management include disciplining students in following the various activities that have been programmed. (3) Student Management Evaluation is carried out through academic and non-academic assessments.